Effects of antibiotic and disinfectant exposure on the mouse gut microbiome and immune function - Wen-Bo Xu; Yun-Fan Wang; Si-Yu Meng; Xiao-Tong Zhang; Yi-Rong Wang; Zhao-Ying Liu (Microbiology Spectrum)
ABSTRACT This study explores the effects of disinfectant and antibiotic exposure on gut health, focusing on gut microbiota balance and gut immune function. Our analysis indicates that disinfectants increase the proportion of Gram-positive bacteria, particularly increasing Staphylococcus levels, while antibiotics increase the proportion of Gram-negative bacteria, especially Bacteroides levels. These changes disrupt microbial harmony and affect the gut microbiome’s functional capacity. Additionally, our research reveals that both disinfectants and antibiotics reduce colon length and cause mucosal damage. A significant finding is the downregulation of NLRC4, a key immune system regulator in the gut, accompanied by changes in immune factor expression. This interaction between chemical exposure and immune system dysfunction increases susceptibility to inflammatory bowel disease and other gut conditions. Given the importance of disinfectants in disease prevention, this study advocates for a balanced approach to their use, aiming to protect public health while minimizing adverse effects on the gut microbiome and immune function.IMPORTANCEDisinfectants are extensively employed across various sectors, such as the food sector. Disinfectants are widely used in various sectors, including the food processing industry, animal husbandry, households, and pharmaceuticals. Their extensive application risks environmental contamination, impacting water and soil quality. However, the effect of disinfectant exposure on the gut microbiome and the immune function of animals remains a significant, unresolved issue with profound public health implications. This highlights the need for increased scrutiny and more regulated use of disinfectants to mitigate unintended consequences on gut health and maintain immune system integrity.